2014
DOI: 10.1016/j.bbalip.2013.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The roles of C-terminal helices of human apolipoprotein A-I in formation of high-density lipoprotein particles

Abstract: Apolipoprotein A-I (apoA-I) accepts cholesterol and phospholipids from ATP-binding cassette transporter Al (ABCA1)-expressing cells to form high-density lipoprotein (HDL). Human apoA-I has two tertiary structural domains and the C-terminal domain (approximately amino acids 190–243) plays a key role in lipid binding. Although the high lipid affinity region of the C-terminal domain of apoA-I (residues 223–243) is essential for the HDL formation, the function of low lipid affinity region (residues 191–220) remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 50 publications
2
35
0
Order By: Relevance
“…Furthermore, the apoA-I-POLARIC concentration dependence of cholesterol effl ux ( K m , 1.8 ± 0.6 g/ml) was consistent with the reported property of wild-type apoA-I ( Fig. 2B ) ( 7,28 ). Therefore, labeling with POLARIC-maleimide affected neither the structure nor the function of apoA-I, and apoA-I-POLARIC possessed the intact ABCA1-dependent HDL formation activity.…”
Section: Application Of Apoa-i-polaric To the Evaluation Of Hdl Formasupporting
confidence: 66%
See 1 more Smart Citation
“…Furthermore, the apoA-I-POLARIC concentration dependence of cholesterol effl ux ( K m , 1.8 ± 0.6 g/ml) was consistent with the reported property of wild-type apoA-I ( Fig. 2B ) ( 7,28 ). Therefore, labeling with POLARIC-maleimide affected neither the structure nor the function of apoA-I, and apoA-I-POLARIC possessed the intact ABCA1-dependent HDL formation activity.…”
Section: Application Of Apoa-i-polaric To the Evaluation Of Hdl Formasupporting
confidence: 66%
“…Concentrated medium was fractionated by gel fi ltration chromatography on a Superdex 200 column calibrated by the proteins of known diameter (particle diameter range, 6.1-17.0 nm), and 1.25 ml fractions were collected ( 28 ). Fluorescence intensity and the amount of cholesterol in each fraction were analyzed as described above and normalized using BSA.…”
Section: Characterization Of Hdl Particles By Gel Fi Ltrationmentioning
confidence: 99%
“…Thus, the helical conformation in this region may result in interaction of H10B with the N-terminal helix bundle. Previous research has also suggested that the C-terminal helix is located near the N-terminal helix bundle and there is interaction between them (25,26,45). Due to the increase in the unfolding cooperativity, the stability of the elongation apoA-I variants is increased or remains similar compared with WT apoA-I (Fig.…”
Section: Circular Dichroism Spectroscopymentioning
confidence: 86%
“…The entire C-terminal domain converts into helical structure upon lipid binding (14). Residues 191-220 play a role in enhancing the ability of apoA-I to bind to and solubilize lipids by forming helix upon lipid interaction (45). All of these studies suggest that the C-terminal domain has a dynamic structure and plays an important role during the lipid-binding process by shifting from disordered into helical structure.…”
Section: The H10b Region Is Vital For the Formation Of Hdl Through Chmentioning
confidence: 89%
See 1 more Smart Citation